Physical Activity in Ovarian Cancer Survivors: Associations With Fatigue, Sleep, and Psychosocial Functioning. Issue 1 (1st January 2009) - Stevinson, Clare; Steed, Helen; Faught, Wylam; Tonkin, Katia; Vallance, Jeffrey K.; Ladha, Aliya B.; Schepansky, Alexandra; Capstick, Valerie; Courneya, Kerry S.
Abstract : Purpose: Physical activity has been associated with better health-related outcomes in several cancer survivor groups but very few data exist for women with ovarian cancer. The purpose of this study was to investigate the associations between physical activity and health-related outcomes in ovarian cancer survivors and to examine any dose-response relationship. Patients and Methods: A cross-sectional postal survey of ovarian cancer survivors on and off treatment identified through the Alberta Cancer Registry was performed. Participants completed self-report measures of physical activity, cancer-related fatigue, peripheral neuropathy, depression, anxiety, and happiness, as well as demographic and medical variables. Results: A total of 359 ovarian cancer survivors participated (51.4% response rate) of whom 31.1% were meeting the public health physical activity guidelines of the Centers for Disease Control and Prevention. Those meeting guidelines reported significantly lower fatigue than those not meeting guidelines (mean difference, 7.1; 95% confidence interval, 5.5-8.8; d = 0.87; P < 0.001). Meeting guidelines was also significantly inversely associated with peripheral neuropathy, depression, anxiety, sleep latency, use of sleep medication, and daytime dysfunction and was positively associated with happiness, sleep quality, and sleep efficiency. There was no evidence of a dose-response relationship beyond meeting or not meeting the guidelines for any variables. Conclusions: Ovarian cancer survivors who were meeting physical activity guidelines reported more favorable outcomes of fatigue, peripheral neuropathy, sleep, and psychosocial functioning.